Multifunctional ZrB2-rich Zr1-xCrxBy thin films with enhanced mechanical, oxidation, and corrosion properties. (March 2021) - Bakhit, Babak; Dorri, Samira; Kooijman, Agnieszka; Wu, Zhengtao; Lu, Jun; Rosen, Johanna; Mol, Johannes M.C.; Hultman, Lars; Petrov, Ivan; Greene, J.E.; Greczynski, Grzegorz
Abstract: Refractory transition-metal (TM) diborides have high melting points, excellent hardness, and good chemical stability. However, these properties are not sufficient for applications involving extreme environments that require high mechanical strength as well as oxidation and corrosion resistance. Here, we study the effect of Cr addition on the properties of ZrB2 -rich Zr1-x Crx By thin films grown by hybrid high-power impulse and dc magnetron co-sputtering (Cr-HiPIMS/ZrB2 -DCMS) with a 100-V Cr-metal-ion synchronized bias. Cr metal fraction, x = Cr/(Zr + Cr), is increased from 0.23 to 0.44 by decreasing the power P ZrB 2 applied to the DCMS ZrB2 target from 4000 to 2000 W, while the average power, pulse width, and frequency applied to the HiPIMS Cr target are maintained constant. In addition, y decreases from 2.18 to 1.11 as a function of P ZrB 2, as a result of supplying Cr to the growing film and preferential B resputtering caused by the pulsed Cr-ion flux. ZrB2.18, Zr0·77 Cr0·23 B1.52, Zr0·71 Cr0·29 B1.42, and Zr0·68 Cr0·32 B1.38 films have hexagonal AlB2 crystal structure with a columnar nanostructure, while Zr0·64 Cr0·36 B1.30 and Zr0·56 Cr0·44 B1.11 are amorphous. All films show hardness above 30 GPa. Zr0.56 Cr0.44 B1.11 alloys exhibit much better toughness, wear, oxidation, and corrosion resistance than ZrB2.18 . This combination of properties makes Zr0·56 Cr0·44 B1.11 ideal candidates for numerous strategic applications. Highlights: ZrB2 -rich Zr1-x Crx By films are grown by hybrid high-power impulse and dc magnetron (Cr-HiPIMS/ZrB2 -DCMS) co-sputtering. Films with x ≤ 0.32 have hexagonal structure with a columnar nanostructure, while alloys with x ≤ 0.44 are amorphous. All films show nanoindentation hardness above 30 GPa. Toughness increases as a function of Cr concentration. Zr0·56 Cr0·44 B1.11 exhibit much better wear, oxidation, and corrosion resistance than reference ZrB2.18 .